Flexible Ureterorenoscopy versus Mini-Percutaneous Nephrolithotomy for the Treatment of Renal Stones - Ergin, Giray; Kirac, Mustafa; Kopru, Burak; Ebiloglu, Turgay; Biri, Hasan (Urology Journal, 2018)
Purpose: To compare the pain status and stone free rates of flexible ureterorenoscopy (F-URS) versus mini-percutaneous nephrolithotomy (mini-PNL) for the treatment of 1-to 2-cm renal stones. Materials and Methods: This study was retrospectively designed with match paired method. Between January 2013 and December 2016, 387 patients underwent stone surgery for renal stones, 45 patients underwent FURS and 45 patients underwent mini-PNL. 90 patients were divided into two groups according to the surgical procedures. Group 1 patients underwent F-URS, and Group 2 patients underwent mini-PNL. During the intraoperative and postoperative periods, pain management for all patients was standardized. Pain scores were determined using a visual analogue scale (VAS) completed at 2, 6, 12 and 24 hours postoperatively. The stone free status, hemoglobin levels, fluoroscopy time (FT), operation time (OT), hospitalization time (HT), return to work time (RWT), and complications were noted for each patient. Results: Of all patients, the mean age was 41.1 ± 12.1 years and the mean stone size was 13.9 ± 2.9 mm. The VAS scores were significantly higher in the mini-PNL group at 2, 6, 12 and 24 hours (P < .05). The stone-free status and complication rates were similar between the two groups (P > .05); however, the hemoglobin decreases and the fluoroscopy, operation, hospitalization and return to work times were higher in the mini-PNL group than in the F-URS group (P < .05). Conclusion: F-URS is less painful than mini-PNL for the treatment of 1- to 2-cm renal stones. However, the stone free rate is similar between the two procedures while mini-PNL is superior in terms of fluoroscopy, operation, hospitalization and return to work duration. We think that F-URS is more comfortable and less painful than mini-PNL and achieves a similar stone free rate for the treatment of 1- to 2-cm renal stones.